Repetition and Alterity: Geoffrey Squires's 'texts for screen'. Issue 1 (May 2016) - Keating, Kenneth
Abstract : This essay examines a number of Geoffrey Squires's recent digital texts which were released in various forms online and later standardised and published together in the Kindle Book Abstract Lyrics and other poems: 2006–2012 . It is contended that Squires embraces computer technology to compose texts which inhabit the screen, but which refuse to adhere to the recently established norms of any of the recognised forms of electronic literature while simultaneously representing something more than the digital conversion of a print text to an ebook. It is argued that these 'texts for screen' thus hold an uneasy position in relation to emerging electronic literature and the more conventional ebook, occupying a problematizing middle ground which at the same time promotes and undermines stability and the author's control over the text. Close readings of a number of these texts reveal that this challenging destabilisation is supported through Squires's utilisation of techniques of repetition which complicates the nature of reproduction and disrupts the critical location of singular meaning in favour of embracing the progressively troubling force of indeterminacy.